NARAI Design Through Instagram Platform and Website as a Media for Youth Campaign in Reducing Waste in Bekasi City - Sopia Raguan; Salsa Solli Nafsika (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Abstract at The problem of waste in Indonesia is never finished, even now waste is a serious problem, especially plastic waste that is difficult to decompose, with the presence of these problems, it is necessary to carry out campaign actions that can provide awareness so that caring actions arise for all parties, this includes making campaign designs on various social media and websites to foster a sense of care in dealing with waste problems. This study uses a qualitative method with a phenomenological approach, the authors make observations to obtain interview data from informants and find out solutions to create the right design for the NARAI program as a media for waste reduction campaigns in Bekasi City. Based on the research data obtained, the authors can design the NARAI program as a waste reduction campaign media, which will produce a website management design, as well as 6 feeds and 4 instastory designs uploaded to NARAI Instagram @naraiwonderland to be well organized and aim to attract public attention. so that information and education can be received properly.